A method for predicting condensation-driven heat removal in a BWR passive containment cooling system - Vierow, Karen M. (Computer Assisted Methods in Engineering and Science, 1994)
Passive designs of several proposed light water reactors rely on containment cooling by condensation heat transfer in a high-concentration, noncondensable gas environment. To evaluate the safety of these plants, methods for analyzing the performance of the cooling systems must be developed. The current study discusses the physics of condensation in the presence of noncondensable gases and a method for predicting the accompanying heat transfer rates based on experimental data. The resulting experimental correlation for heat transfer coefficients has been implemented into the TRACG code, and a specific application has been made to the Simplified Boiling Water Reactor for conditions following a Design Basis Accident LOCA (Loss-or-Coolant Accident)